Easy Control Procedures for Radio-Iodinated Human Serum Albumin and their Practical Importance - Eston, Veronica R.; Zinner, Klaus; Tavares, Yolanda; Eston, Tede (Nuklearmedizin - NuclearMedicine, 1962)
1. Two shipments of radio-iodinated human serum albumin (RISA), produced by different commercial laboratories, were analysed by ascending and circular chromatography, electrophoresis, autoradiography and radioactive scanning.2. Both shipments were subdivided into three samples and each kept under slightly different conditions, in order to study the best conditions for storage of the product.3. Results obtained showed progressive albumin denaturation in both shipments, with the formation of radioactive degradation products and radioactive iodide. This process of radiolysis was less intense in the samples maintained permanently in the refrigerator and handled as little as possible.4. The extent of alteration induced was smaller when the protein concentration was around 5 mg per ml and the initial radioactivity less than 0.8 mCper ml.5. The results obtained show the need for a frequent control of the albumin, not only in relation to the iodide liberated, but also with respect to degradation of the albumin by radiolysis.6. Circular chromatography followed by autoradiography is the simplest method of control which can be easily performed in any clinical laboratory.1. Deux parties de sérum albumine humaine marquée par le I131 (RISA), produites par de differents laboratoires, ont été annalysées par chromatographie ascendente et circulaire, électrophoresis, autoradiographie et “scanning“ radioactif.2. Les deux parties ont été subdivisées en trois échantillons et chacun a été gardé dans des conditions differents pour étudier les meilleurs conditions de magasinage du produit.3. Les résultats ont démontré la dénaturation progressive de l’albumine avec la formation de produits de dégradation radioactif et de iodine radioactif. Ce procédé de radiolyse est moins intense avec les échantillons qui sont maintenus constamment dans le réfrigérateur et sont manipulés le moins possible.4. L’extension de l’altération produite est moins intense quand la concentration de proteïne est environ 5 mg par ml et la radioactivité initiale moins de 0,8 mC par ml.5. Les résultats démontrent la nécessité d’un contrôle fréquent de l’albumine autant pour le iodide radioactif liberé que pour les produits de dénaturation de l’albumine.6. La chromatographie circulaire avec l’autoradiographie est la méthode de contrôle la plus simple et facile à être executée dans les laboratoires cliniques.1. Zwei Sendungen von menschlichem, mit I131 markiertem Serum Albumin (RISA), die von verschiedenen Laboratorien erzeugt wurden, wurden mittels aufsteigender und zirkulärer Chromatographie, Elektrophoresis, Autoradiographie und radioaktivem “Scanning“ untersucht.2. Beide Sendungen wurden in drei Proben geteilt und jede wurde unter verschiedenen Verhältnissen aufgehoben, um die besten Lagerungsbedingungen des Produktes zu analysieren.3. Die erhaltenen Resultate ergaben eine progressive Denaturierung des Albumins in beiden Proben mit Bildung von radioaktiven Produkten und freiem Jodid. Dieser radiolytische Prozeß war geringer in jenen Proben, die dauernd im Eisschrank gelagert waren und so wenig wie möglich gehandhabt wurden.4. Die Intensität der Veränderungen war geringer, wenn die Protein-Konzentration etwa 5 mg per ml und die ursprüngliche Radioaktivität des Materials weniger als 0,8 mC per ml betrug.5. Die Resultate beweisen, daß eine häufige Kontrolle des RISA nötig ist, nicht nur wegen des freien Jodides, sondern auch wegen der Veränderungen des Albumins durch die Einwirkung der Radioaktivität.6. Zirkuläre Chromatographie mit Autoradiographie ist die einfachste Kontrollmethode, die leicht in jedem klinischen Laboratorium ausgeführt werden kann.